Toxic effects of antimony in plants: Reasons and remediation possibilities—A review and future prospects - Tang, Haiying; Meng, Guiyuan; Xiang, Junqing; Mahmood, Athar; Xiang, Guohong; SanaUllah; Liu, Ying; Huang, Guoqin (Frontiers in plant science, 2022)
Antimony (Sb) is a dangerous heavy metal (HM) that poses a serious threat to the health of plants, animals, and humans. Leaching from mining wastes and weathering of sulfide ores are the major ways of introducing Sb into our soils and aquatic environments. Crops grown on Sb-contaminated soils are a major reason of Sb entry into humans by eating Sb-contaminated foods. Sb toxicity in plants reduces seed germination and root and shoot growth, and causes substantial reduction in plant growth and final productions. Moreover, Sb also induces chlorosis, causes damage to the photosynthetic apparatus, reduces membrane stability and nutrient uptake, and increases oxidative stress by increasing reactive oxygen species, thereby reducing plant growth and development. The threats induced by Sb toxicity and Sb concentration in soils are increasing day by day, which would be a major risk to crop production and human health. Additionally, the lack of appropriate measures regarding the remediation of Sb-contaminated soils will further intensify the current situation. Therefore, future research must be aimed at devising appropriate measures to mitigate the hazardous impacts of Sb toxicity on plants, humans, and the environment and to prevent the entry of Sb into our ecosystem. We have also described the various strategies to remediate Sb-contaminated soils to prevent its entry into the human food chain. Additionally, we also identified the various research gaps that must be addressed in future research programs. We believe that this review will help readers to develop the appropriate measures to minimize the toxic effects of Sb and its entry into our ecosystem. This will ensure the proper food production on Sb-contaminated soils.